Sex trafficking inside the business of modern slavery - Kara, Siddharth (Columbia University Press, 2009)
"Kara supplements his analysis with a riveting account of this unconscionable industry, sharing the moving stories of victims and revealing the shocking conditions of their exploitation. He concludes with a proposal for aggressive measures that target the essential business and economic functioning of the sex trafficking industry designed to provide a more effective global approach to abolishing these crimes against the world's most vulnerable and exploited persons."--Jacket.